Randomised controlled trials as part of clinical care: A seven‐step routinisation framework proposal. Issue 2 (19th December 2018) - Team, Victoria; Weller, Carolina D.
Abstract : Evidence translation in wound care relies on the need for evidence generation. Clinical practice may generate evidence only if evidence‐generating research projects, such as randomised controlled trials (RCTs), became routinised in clinical settings. The aim of this study was to identify optimal trial‐related practices to routinise trial‐related activities in Melbourne‐located wound clinics as reported by clinicians and researchers. We conducted a secondary analysis of the available data on how to routinise RCTs in clinical care, with a focus on enablers and suggestions provided by the participants during face‐to‐face and telephone interviews. Data were obtained from a qualitative observational study nested within a randomised, double‐blinded, placebo‐controlled trial on clinical effectiveness of aspirin as an adjunct to compression therapy in healing chronic venous leg ulcers (ASPiVLU). We developed a seven‐step Routinisation of Trials in Clinical Care Framework. These steps include: (1) pre‐trial clinical site assessment, (2) optimising pre‐recruitment arrangements, (3) developing and updating trial‐related skills, (4) embedding RCT recruitment as part of routine clinical care, (5) promoting teamwork and trial‐related collaboration, (6) addressing trial‐related financial issues, and (7) communicating trial results to clinicians.